Pengaruh Aktivitas Fisik terhadap Kualitas Tidur pada Anak dengan Autism Spectrum Disorders (ASD) - Trivansyah, Nurina Kaffawati Nur; Saloko, Erayanti (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Children with autism often experience sleep disturbances with normal development. Physical activity is known as one of the recommended non-pharmacological interventions to improve sleep quality. Objectives: This study aims to determine the effect of physical activity on sleep quality in children with Autism Spectrum Disorder (ASD). Methods: Quantitative study of quasi-experimental model with non-random pretest-posttest with control group design. The sample of this study was 30 ASD children aged 4-17 years and had sleep disturbances through measurement with The Children's Sleep Habits Questionnaire (CSHQ) instrument. The intervention group received a home jogging/walking program for 3 weeks with a duration of 30 minutes each day. The control group did daily physical activities as usual. Results: The results of data analysis using paired t-test in the intervention group obtained a p-value of 0.00 (<0.05) so that it was known that there was a difference in the average pretest-posttest score of sleep quality. The results of data analysis using paired t-test in the control group obtained a p-value of 0.057 (> 0.05) so that it is known that there is no difference in the average score of pretest-posttest sleep quality. The results of data analysis using independent t-test obtained a p-value of 0.00 (<0.05). Conclusion: This shows that there is a significant difference between the intervention group and the control group and the provision of physical activity in the form of a home jogging/walking program has an effect on sleep quality in children with ASD Keywords : Keywords: Sleep quality, Physical activity, Autism Spectrum Disorder (ASD)